2010
DOI: 10.1111/j.1460-9568.2010.07366.x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of allocation of spatial attention by acoustic cues in non‐human primates

Abstract: Spatial attention mediates the selection of information from different parts of space. When a brief cue is presented shortly before a target (cue to target onset asynchrony = CTOA) in the same location, behavioral responses are facilitated, a process called attention capture. At longer CTOAs responses to targets presented in the same location are inhibited, called inhibition of return (IOR). In the visual modality, these processes have been demonstrated in both humans and non-human primates, the latter allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 46 publications
3
8
1
Order By: Relevance
“…The brain reconstructs the spatial location of an auditory stimulus based on interaural and monaural auditory cues (Blauert & Lindemann, 1986), and the output of this computation is typically less precise than the localization of a visual stimulus. Studies on animals (Lee & Middlebrooks, 2010;Populin & Rajala, 2010) and humans (Pavani, Làdavas, & Driver, 2002) have also shown that localization of sounds is most precise when the spatial encoding of the auditory stimuli is salient for the task. In cats, Lee and Middlebrooks (2010) showed that the width of spatial receptive fields (from 180°to 360°) of neurons in the auditory primary cortex (A1) becomes sharper when the localization of sounds is requested by the task, as compared to when spatial factors are not salient for the animal's behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The brain reconstructs the spatial location of an auditory stimulus based on interaural and monaural auditory cues (Blauert & Lindemann, 1986), and the output of this computation is typically less precise than the localization of a visual stimulus. Studies on animals (Lee & Middlebrooks, 2010;Populin & Rajala, 2010) and humans (Pavani, Làdavas, & Driver, 2002) have also shown that localization of sounds is most precise when the spatial encoding of the auditory stimuli is salient for the task. In cats, Lee and Middlebrooks (2010) showed that the width of spatial receptive fields (from 180°to 360°) of neurons in the auditory primary cortex (A1) becomes sharper when the localization of sounds is requested by the task, as compared to when spatial factors are not salient for the animal's behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Two adult male rhesus monkeys (Macaca mulatta), weighing 7.5 and 10 kg, participated in this study. One of them, subject G, had contributed to our previous behavioral report (Populin and Rajala 2010). The animals were prepared for eye movement recordings with the scleral search coil technique (Robinson 1963) by implanting coils constructed from teflon-coated stainlesssteel wire (SA632; Cooner Wire, Chatsworth, CA), using the approach described by Judge et al (1980).…”
Section: Methodsmentioning
confidence: 99%
“…Using gaze latency as the dependent variable, our data demonstrated that rhesus monkeys could indeed allocate spatial attention based on auditory spatial information. Moreover, they showed that the effects followed the classical attention capture (AC) (Jonides 1981) and inhibition of return (IOR; Posner and Cohen 1984) pattern that characterizes the allocation of spatial attention in the visual modality, albeit with a faster time course (Populin and Rajala 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations